Possible effects of in-service education on EFL teachers' professional development in terms of teacher efficacy and reflective thinking - Özçallı, Sema. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
Possible Effects of In-service Education on EFL Teachers’ Professional Development in terms of Teacher Efficacy and Reflective Thinking By Sema Özçallı The purpose of this study was to analyze the relationship between teacher efficacy and reflective thinking, and the impact of an in-service education program on teacher efficacy and professional development in terms of reflective thinking. Twenty five in-service teachers from five foundation schools in Istanbul participated in this study. Multiple sets of data for this study came from: (a) questionnaires, (b) interviews, and (c) teacher journals. Collection of data was completed in two consecutive semesters, Fall 2005 and Spring 2006. The present study investigated the following research questions: 1. Is there an impact of an in-service teacher education program on Turkish EFL teachers’ efficacy and their reflective thinking? If so, how? 2. Is there a relationship between teacher efficacy and reflective thinking? Results indicated that teacher efficacy and reflective thinking had no significant relation with each other. The in-service education program had a positive impact on teacher efficacy. However, although there was an improvement in these particular teachers’ reflective thinking as a result of the in-service education program, this was not statistically significant. On the other hand, in one-to-one interviews, the teachers stated that journals allowed them to be reflective and to make connections between theory and practice, which helped them to think about their strengths and weaknesses as teachers. Based on the findings, the data supported v Hatton and Smith’s view of teachers’ reflective thinking as a hierarchical developmental sequence.
Keywords: English teachers -- Turkey.; English language -- Study and teaching -- Foreign speakers.; Self-efficacy.; Reflective teaching.; Teachers -- In-service training.